Helius: A Design Thinking Techniques Recommendation System in Software Development - Parizi, Rafael; Hanauer, Lucas; Marczak, Sabrina; Conte, Tayana (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2024)
This paper demonstrates Helius, a collaborative Design Thinking (DT) techniques recommendation system. We proposed Helius to support DT practitioners in selecting DT techniques for use in software development, as literature has shown that selecting a set of DT techniques can be a complex decision-making problem. To develop Helius, we followed a Design Science Research framework, starting with a deep understanding of the problem and followed by three iterations of design and validation activities. In total, 40 professionals participated in the validation activities for Helius. The results show that Helius effectively supports the selection of DT techniques and is considered by DT practitioners to be a useful and easy-to-use recommendation system. Helius Tool’s video:  https://doi.org/10.5281/zenodo.11398135